Aplicações do Teacher Behavior Checklist à formação e avaliação de professores de nível superior: contribuições analítico-comportamentais e psicométricas - Henklain, Marcelo Henrique Oliveira (Universidade Federal de São Carlos, 2017)
The training and evaluation of teaching for college teachers still needs to be deepened in relevant aspects, such as the instrumentalization of the teacher so that he is able to improve himself in his work. A feasible proposal to contribute to the improvement of teaching practice is to use the Teacher Behavior Checklist (TBC), adapted to be fulfilled by students, as an auxiliary tool to conduct teacher’s formative assessment. Research in several countries has shown that teachers and students consider TBC representative of what an effective teacher does to teach, and psychometric evidence supports its use for this teacher assessment modality. The general objective of this research was to investigate evidence of validity and reliability of the TBC for the Brazilian university culture and to identify possibilities of the contribution of this instrument for the teachers training. This work was organized into five studies. Study 1 described the TBC’s adaptation process and presented evidence favorable to the use of this adapted version. Study 2 presented evidence of the content validity of this TBC version by means of two studies with Brazilian professors and undergraduates. The objective of the first one was to evaluate the degree of relevance of the TBC items and it showed that all items were considered very relevant. The second study investigated which are the 10 most important qualities of the TBC. Results indicated possibilities of approximation among the selection standards presented by students and teachers from Brazil and other countries, suggesting the feasibility of thinking about teaching practices useful for different college student’s cultures. Study 3 aimed to investigate evidence of validity and reliability of the current version of TBC. Results provided support for a two-factor model of TBC, similar to those proposed by the authors of the instrument. This makes it possible to compare data collected in Brazil and in the USA. Evidence of reliability has been documented, for example, through the Test-Retest procedure. In Study 4 the objective was to investigate whether the evidence of validity and reliability could be verified with samples from different geographical regions of Brazil, as well as to evaluate whether the present version of the TBC would allow identifying teachers with different degrees of teaching repertoires. The results provided support for the understandings formulated in Study 3 and evidence has been documented that TBC allows distinguishing between different quality degrees of teaching repertoires. In Study 5 an interpretation of the TBC items as behavior classes was presented and a description of the functional parts of three items of the instrument was carried out. Information that was not highlighted in the instrument and that is necessary for the planning of teacher training have been identified. It became clear that TBC can be used as a source to derive teaching objectives for teacher training. Cumulative evidence suggest that TBC can be used in future studies to investigate teacher education and assessment, and can be tested in an applied context as an auxiliary tool for the formative assessment of college teachers.
Teacher Behavior Checklist applications to the training and assessment of higher education teachers: behavior-analytic and psychometrical contributions
Keywords: Evidências de validade e de fidedignidade; Avaliação docente; Formação docente; Ensino Superior; Evidences of validity and reliability; Teacher Behavior Checklist; Teacher training; Teacher assessment; Higher education; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM